Talking through the continuum: New manifestations of Fano‐resonance phenomenology realized with mesoscopic nanostructures. Issue 2 (6th June 2012) - Xiao, S.; Xiang, S.; Yoon, Y.; Kang, M.‐G.; Kida, M.; Aoki, N.; Reno, J.L.; Ochiai, Y.; Mourokh, L.; Fransson, J.; Bird, J.P.
Abstract: The focus of this review is recent work in which we have demonstrated a highly‐flexible approach to the study of Fano‐resonance phenomena, by making use of the mesoscopic devices known as quantum point contacts (QPCs). Utilizing the ability of these structures to function as an "on‐demand quantum state", we demonstrate a highly‐flexible system for the investigation of Fano resonances. Our approach involves making measurements of non‐locally coupled pairs of QPCs, one of which is used to form the discrete state needed for the Fano resonance, while the other serves as a detector whose conductance is sensitive to the energy of this state. As a demonstration of the flexibility of this approach, we show how it can be used to implement a "multi‐state" Fano resonance, in which two discrete states undergo a robust interaction that is achieved by coupling them to each other through a common continuum.